1980
DOI: 10.1111/j.1476-5381.1980.tb07035.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphine and Supraspinal Inhibition of Spinal Neurones: Evidence That Morphìne Decreases Tonic Descending Inhibition in the Anaesthetized Cat

Abstract: 1 A study was made in cats anaesthetized with barbiturate or a-chloralose, of the excitation of dorsal horn neurones by impulses in unmyelinated (C) primary afferent fibres of the tibial nerve. 2 Block of conduction in the first lumbar segment by cooling produced large increases in the number of action potentials evoked by C fibre afferents in neurones of more caudal segments. 3 Morphine (0.3 to 1.0 mg/kg) reduced the excitation of neurones by C fibre afferents and also reduced the increase produced by blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 22 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…morphine (IlIrd ventricle) induced dosedependently a facilitation of C-fibre-evoked responses of dorsal horn convergent neurones over a 0.6-40 jig dose range (Bouhassira et al, 1986). Other authors, studying the microinjection of morphine into NRM, intracerebroventricular morphine and systemic morphine in the presence and absence of reversible block of descending controls have reached similar conclusions (Duggan et al, 1980;Sinclair 1984;Llewellyn et al, 1986). However, experiments in the cat with PAG and NRM morphine (Gebhart et al, 1984;Du et al, 1984) and another in the rat with PAG microinjection (Bennett & Mayer, 1979) have shown opiate inhibition of dorsal horn cells.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…morphine (IlIrd ventricle) induced dosedependently a facilitation of C-fibre-evoked responses of dorsal horn convergent neurones over a 0.6-40 jig dose range (Bouhassira et al, 1986). Other authors, studying the microinjection of morphine into NRM, intracerebroventricular morphine and systemic morphine in the presence and absence of reversible block of descending controls have reached similar conclusions (Duggan et al, 1980;Sinclair 1984;Llewellyn et al, 1986). However, experiments in the cat with PAG and NRM morphine (Gebhart et al, 1984;Du et al, 1984) and another in the rat with PAG microinjection (Bennett & Mayer, 1979) have shown opiate inhibition of dorsal horn cells.…”
Section: Discussionmentioning
confidence: 77%
“…Direct testing of this premise, gauging the effects of microinjections of morphine on dorsal horn neurones has led to conflicting results. Two groups have reported neuronal depression following morphine microinjected into the periaqueductal grey matter (PAG) (Bennett & Mayer, 1979;Gebhart et al, 1984) whereas we have found contrary results (Dick- 'Author for correspondence at University College, London. enson & Le as have other groups using either brainstem microinjections (Llewellyn et al, 1986), intracerebroventricular administration (Sinclair, 1984;Bouhassira et al, 1986) or other experimental approaches such as reversible block of descending inhibition in the presence of morphine (Duggan et al, 1980). In our previous studies we have used 5 ptg of morphine in the microinjection, a dose effective in behavioural testing of analgesia in rats (Yaksh & Rudy, 1978;Dickenson & Le Bars, unpub-lished results).…”
Section: Introductionmentioning
confidence: 86%
“…Their proposed dual modulatory mechanisms were based on electrophysiological studies on sensory dorsal root ganglion neurons that show that -opioid agonists can evoke prolongation (12,49) or shortening (11,24,38,60) of the action potential of these cells when applied at low and high concentrations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The most convincing is the demonstration that microinjection of etorphine was no more effective in decerebrate, non-anaesthetized cats than it was in intact, anaesthetized preparations. This is supprted by the observation that electrical stimulation of the brainstem as readily inhibits noxious heat-evoked responses in anaesthetized cats (Belcher et (Duggan et al, 1980) have shown that tonic descending inhibition is present in pentobarbitoneanaesthetized cats.…”
Section: Discussionmentioning
confidence: 99%
“…However, attempts to show directly that opiates increase descending inhibitory control of spinal neurones have not always been successful. Thus Duggan, Griersmith & North (1980) have shown that systemically administered morphine attenuates, rather than increases, tonic descending inhibition in cats and LeBars et al (1980a) failed to demonstrate inhibition of dorsal horn neurones by microinjection to nucleus raphe magnus (NRM) of morphine in rats, employing doses which cause analgesia. In contrast, Bennett & Mayer (1979) found that microinjection of etorphine or morphine in the periaqueductal grey (PAG) in rats does inhibit the excitation of dorsal horn neurones in anaesthetized rats and Gebhart, Sandkuhler, Thalhammer & Zimmermann (1982) have recently observed similar effects with morphine in cats.…”
Section: Introductionmentioning
confidence: 99%